Attitude of Nurses towards Care of Elderly People in TU Affiliated Teaching Hospitals of Kathmandu Valley - Upadhyay, Radhika; Shakya, Suraj; Pahari, Durga Prasad (Health Prospect, 2020)
Nurses play an essential role in the provision of health services and health promotion for the elderly people. This study aims to find out the attitude of nurses towards care of elderly people in Tribhuvan University affiliated teaching hospitals of Kathmandu valley, Nepal. A descriptive cross-sectional study was conducted among 236 nurses working in TU affiliated teaching hospitals in Kathmandu. Data was collected proportionately from four hospitals using semi structured questionnaire and “Multifactor Attitudes Questionnaires (MAQ)” for assessing attitude of nurses towards care of elderly. Data was entered in EpiData 3.1 and analyzed using SPSS version 16. Descriptive as well as inferential statistics namely Kruskal-Wallis and Man-Whitney test were used for analyzing data. The overall response rate was 98% (236 out of 240 nurses). The mean age of respondents was 28.74 ±7.43 years. The overall prevalence of attitude below than median value of the scale was 2.5% and more than half (51.3%) of respondents had knowledge below median value regarding care of elderly. Attitude towards elderly was found to be associated with age, working hour and qualification of the respondent. So these factors should be considered in nursing education and to improve attitude towards care of elderly people. Keywords: Attitude, Nurse, Care, Elderly, Kathmandu